Foreword - Vanegas Zubiría, Carlos Mario (Estudios de Filosofía, 2018)
Modernity, starting with early Romanticism and the French Revolution, put the traditional relationship between art and politics in crisis. If one of the functions of art had been the expression and legitimation of power in social and political history, in so many possibilities that presented future expectations for culture, artists began to differentiate and separate themselves from the public by questioning the anonymous market linked to political commitment, the brutal instrumentalization of art at the service of revolutionary politics and utopia, and moving away from any hopeful vision of social transformation. A journey that can be understood as a history of tensions and options in the face of politics that still marks the dominant representations of art today.